Prefácio e Organização - Conte, Tayana; Albuquerque, Adriano Bessa; Barcellos, Monalessa Perini (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2019)
On behalf of the organizing committee, we would like to extend our warmest welcome to the 17th Brazilian Symposium on Software Quality (SBQS 2018) in the “Ecological Capital of Brazil”. The SBQS is the main Brazilian forum devoted to Software Quality. Software quality manifests in two complementary and dependent aspects: Process Quality and Product Quality. Due to the current dependence on software and value-added services, research on software quality and its application to products and services is both a necessity and a differential to provide value to organizations and their business.